Plan of Action (PoA) in Hospital Management: Urgency, Challenges, and Implementation - Muhammad Rafli Ramadhan; Darmawati Sahafi; Khleg Gamal Mohammed Al-Yamani; Budi Hartono (Persatuan Dosen Kesehatan Masyarakat, 2026)
Abstract: The Plan of Action (PoA) is an operational planning instrument that plays a crucial role in ensuring the achievement of organizational objectives, including in hospitals. PoA helps translate strategic plans into concrete, measurable, and systematic actions. This article aims to examine the concept of PoA based on various references, identify the urgency and challenges of its implementation in hospitals, describe the components and stages of PoA development, and review relevant journals on PoA implementation in hospital settings. The method employed is a literature review of management textbooks and health-related journal articles. The findings indicate that PoA is a critical element in improving service quality and management efficiency in hospitals, despite facing challenges such as limited resources, complex coordination, and organizational commitment. Keywords: Plan of Action, Hospital Management, Operational Planning, Service Quality